Wheelchair pushrim kinetics measurement: A method to cancel inaccuracies due to pushrim weight and wheel camber. (February 2017) - Chénier, Félix; Aissaoui, Rachid; Gauthier, Cindy; Gagnon, Dany H.
Highlights: Wheelchair propulsion kinetics can be recorded with instrumented wheels. Measurement accuracy is affected by wheel camber or pushrim weight alterations (errors up to 9 N). A new, automatic method to correct these inaccuracies is presented. This method does not need additional acquisitions and can be applied directly on existing data. The method was validated with 9 wheelchair users propelling overground at a natural velocity. Abstract: The commercially available SmartWheel TM is largely used in research and increasingly used in clinical practice to measure the forces and moments applied on the wheelchair pushrims by the user. However, in some situations (i.e. cambered wheels or increased pushrim weight), the recorded kinetics may include dynamic offsets that affect the accuracy of the measurements. In this work, an automatic method to identify and cancel these offsets is proposed and tested. First, the method was tested on an experimental bench with different cambers and pushrim weights. Then, the method was generalized to wheelchair propulsion. Nine experienced wheelchair users propelled their own wheelchairs instrumented with two SmartWheels with anti-slip pushrim covers. The dynamic offsets were correctly identified using the propulsion acquisition, without needing a separate baseline acquisition. A kinetic analysis was performed with and without dynamic offset cancellation using the proposed method. The most altered kinetic variables during propulsion were the vertical and total forces, with errors of up to 9 N ( p  < 0.001, large effect size of 5). This method is simple to implement, fully automatic and requires no further acquisitions. Therefore, we advise to use it systematically to enhance the accuracy of existing and future kinetic measurements.